Laparoendoscopic single-site nephrectomy for hemodialysis patients with dialysis-related renal tumors. Issue 3 (4th May 2018) - Takei, Kohei; Yamasaki, Mutsushi; Abe, Satoki; Yamanaka, Naoyuki; Sejiyama, Shinya; Narimatsu, Takahiro; Hata, Shinro; Shibuya, Tadamasa; Hirai, Kenichi; Ando, Tadasuke; Shin, Toshitaka; Mori, Kenichi; et al.
Abstract: Purpose: The purpose of this study is to assess the efficacy of laparoendoscopic single-site (LESS) nephrectomy in hemodialysis patients, we compared outcomes between LESS nephrectomy and conventional laparoendoscopic nephrectomy in hemodialysis patients with dialysis-related renal tumors. Material and methods: A total of 16 hemodialysis patients who underwent LESS nephrectomy (LESS-N; n = 8) or conventional laparoendoscopic nephrectomy (C-N; n = 8) between November 2003 and July 2012 were retrospectively evaluated. Outcomes were compared between the two groups. Results: Patient and tumor characteristics were similar between the LESS-N and C-N groups. The mean operative duration was longer in the LESS-N than in the C-N group (231.0 ± 26.7 min versus 188.6 ± 36.4 min; p = .025). The mean estimated blood loss was lower in the LESS-N compared with the C-N group (26.4 ± 14.4 ml versus 65.6 ± 45.2 ml; p = .047). Postoperative complications were observed in three cases, comprising one case of retroperitoneal hematoma in the LESS-N group and one case each of peritoneal hematoma and retroperitoneal abscess in the C-N group. Surgical scarring was minimal in the LESS-N group. Conclusions: Although there is a little extension of the operating time, LESS nephrectomy in hemodialysis patients is a feasible procedure compared with the conventional method.